Keharmonisan Keluarga, Konsep Diri dan Interaksi Sosial Remaja - Yunistiati, Farida; Djalali, M. As'ad; Farid, Muhammad (Persona:Jurnal Psikologi Indonesia, 2014)
Abstract. This study aims to examine the relationship between family harmony and self-concept of the adolescent social interaction in vocational students. The population in this study were students of SMK PGRI 3 Madiun class XII, 173 students and tested answers after totaling 157 eligible students. Collecting data using a scale of family harmony, self-concept scale and social interaction made by researchers. Data analysis method used is multiple regression analysis techniques to be treated with the help of computer statistical program SPSS 18 series. Testing multiple regression analysis obtained R = 0.103 and F of 8.841 to p = 0.000 (P < 0.05), which means that family harmony and self-concept has a significant relationship with adolescent social interaction. The results of the analysis of the correlation between family harmony with social interaction indicates t = 3.541 and p = 0.001 (p < 0.05), which means there is a significant positive correlation between family harmony with social interaction. The result of the analysisof correlation between self-concept and social interaction showed t = 1.187 and p = 0.237 (p > 0.05), which means there is no significant correlation betweenself-concept and social interaction. R square = 0.103 shows that the two independent variables self-concept and family harmony together to contribute effectively to the social interactions of adolescents are 10.299% and 89.701% of orther variables influence adolescent social interaction dependent variable in this study.Keywords : harmony family, self-concept, social interaction.